The Implementation of Role Play Technique to Enhance EFL Students’ Speaking Skill - Fiani, Ani; Nahak, M Maria Ignasia (STKIP PGRI Lubuklinggau, 2025)
Speaking remains an important but difficult skill for EFL learners due to the fear of being assessed and not having the opportunity for hands-on practice. In this study, 24 peer-reviewed articles from 2022–2025 were examined. The study employed a qualitative descriptive library research approach. Based on the findings, role-playing significantly enhanced students' confidence, vocabulary, pronunciation, and fluency by offering a secure and engaging setting. Furthermore, it reduces language anxiety and promotes imaginative and cooperative activities. It is primarily implemented through the use of structured group activities, reflective follow-up, and realistic scenarios. According to this study, role-playing enhances students' social and psychological growth as well as their language proficiency. Consequently, it is strongly advised that role play be used frequently in EFL classes.